The Effect Of Compensation And Work Discipline On Employee Performance In PT. Nusantara Inti Solusindo South Jakarta - Bahri, Samsul; Irwansyah, Irwansyah (Pascasarjana Universitas Pasundan, 2025)
The purpose of this study is to determine the effect of compensation and work discipline on employee performance at PT. Nusantara Inti Solusindo South Jakarta. The method used is quantitative. The sampling technique uses saturated sampling and obtained a sample of 65 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study show that compensation has a significant effect on employee performance with the value of the regression equation Y = 10.308 + 0.741X1, the correlation coefficient value obtained is 0.755, meaning that the two variables have a strong level of relationship. The results of the determination or contribution of the influence are 56.9% while the remaining 43.1% is influenced by other factors. The hypothesis test obtained a calculated t value > t table or (9.129 > 1.998). Thus, H0 is rejected and H1 is accepted. Work discipline has a significant effect on employee performance with the values of the regression equation Y = 11,986 + 0.702 X2, the correlation coefficient value of 0.655 means that the two variables have a strong level of relationship. The value of determination or contribution of influence is 0.429 or 42.9% while the remaining 57.1% is influenced by other factors. The left-hand side hypothesis test obtained a calculated t value > t table or (6.877 > 1.998). This is also strengthened by a significance value <0.050 or (0.001 <0.050). Thus, H0 is rejected and H2 is accepted. Compensation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 4.502 + 0.555X1 + 0.340 X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is obtained at 0.634 meaning that it has a strong relationship. The coefficient of determination or contribution of its simultaneous influence is 63.4% while the remaining 36.6% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (53.792 > 2.750), this is also strengthened by a significance of < 0.050 or (0.000 < 0.050). Thus, H0 is rejected and H3 is accepted.